Estudo da terapia por fotobiomodulação associada ao diazepam no controle da alodinia e na modulação de receptores de dor em modelo experimental de tendinite - Silva, Yose Marie Elizabeth e (2021)
Pain is an unpleasant sensory and emotional experience and is the main reason for seeking specialized treatment. Pains related to tendinopathies are frequent and difficult to be treated and photobiomodulation therapy (PBM) has shown promising results in controlling inflammation and pain. Since benzodiazepines are used in the auxiliary treatment of chronic pain, this research aimed to study the effect of PBM therapy associated with Diazepam, a gabaergic receptor agonist, on the modulation of allodynia, as well as to determine the mechanisms of action involved. Methodology: Male Wistar rats were distributed in seven (7) experimental groups, namely: I- Healthy Control Group (CTL); II- Untreated Tendinitis Group (NT); III- Tendinitis group treated with Photobiomodulation (PBM) in the parameters of 810 nm, 3 J, 100 mW; IV-Diazepam-treated Tendinitis Group (DZP); V- Tendinitis group treated with PBM associated to DZP (PBM + DZP) , VI- Tendinitis group treated with Diazepam associated to Flumazenil (FLU + DZP) and VII- Tendinitis Group treated with Flumazenil associated to PBM (FLU + PBM). Tendinitis was induced from the transcutaneous injection of collagenase type I in the region of the calcaneus tendon and the treatments were administered according to the description of each experimental group. After 8 hours of tendinitis induction, local allodynia was measured. At the end of the experiment, the animals were euthanized and the tendons removed for analysis. Gene expression of B1, NK1, GABAα1, GABAα2 receptors and myeloperoxidase (MPO) levels were evaluated. Results: Treatment with PBM reduced the gene expression of B1 and NK1 receptors. Both MPO levels and mechanical allodynia were also reduced in the PBM group. The PBM + DZP group reduced the expression of B1, MPO and mechanical allodynia receptors. The FLU + PBM group showed a worsening in the expression of all receptors when compared to the PBM group. Conclusions: Our results demonstrate that photobiomodulation therapy helps to control pain and the mechanisms associated with this pain control are also related to the modulation of B1, NK1, GABAα 1 and GABAα2 receptors in addition to controlling the inflammatory process. In addition to the well-known action of phototherapy in reducing pain by modulating₁ the inflammatory process, this study demonstrated that FBM acts on GABAα receptors, helping in the process of sedation and partial pain control. The relationship between these mechanisms still deserves to be investigated, since the work for most of these mechanisms is scarce.